2019
DOI: 10.3758/s13414-019-01721-8
|View full text |Cite
|
Sign up to set email alerts
|

Do we remember templates better so that we can reject distractors better?

Abstract: Feature Integration Theory proposed that attention shifted between target-like representations in our visual field. However, the nature of the representations that determined what was target like received less specification than the nature of the attention shifts. In recent years, visual search research has focused on the nature of the memory representations that we use to guide our shifts of attention. Sensitive measures of memory quality indicate that the template representations are remembered better than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(57 citation statements)
references
References 51 publications
(57 reference statements)
5
49
3
Order By: Relevance
“…Using a visual search task for a target amongst linearly separable distractors, the results demonstrate that early attentional guidance was a coarse process mainly based on "relational" sensory information, whereas subsequent match decisions were compared against a more precisely tuned template centered on an "optimal" offtarget feature. Although previous studies have found evidence for coarse guidance (Anderson, 2014;Kerzel, 2019;Martin & Becker, 2018) and precise decisions (Rajsic & Woodman, 2020) separately, our experiments provide direct evidence that the informational content of the target template is used differently on these two subprocesses of visual search.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…Using a visual search task for a target amongst linearly separable distractors, the results demonstrate that early attentional guidance was a coarse process mainly based on "relational" sensory information, whereas subsequent match decisions were compared against a more precisely tuned template centered on an "optimal" offtarget feature. Although previous studies have found evidence for coarse guidance (Anderson, 2014;Kerzel, 2019;Martin & Becker, 2018) and precise decisions (Rajsic & Woodman, 2020) separately, our experiments provide direct evidence that the informational content of the target template is used differently on these two subprocesses of visual search.…”
Section: Discussioncontrasting
confidence: 71%
“…This process must be more precise in order to know whether an item is the same as the target or just similar. Unlike attentional guidance, the importance of this decision process on visual search has only been explored more recently (Bravo & Farid, 2014;Hout & Goldinger, 2015;Malcolm & Henderson, 2009;Rajsic & Woodman, 2020;Wolfe, 2012). In the current study, we used fixation dwell times (Experiment 1) and the DDM drift rates modeled from accuracy and RT (Experiment 2) as measurements of target-match decisions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In doing so, it is possible to submit the distribution of memory errors to modeling and to identify different sources of error. While a number of models have been proposed to decompose such data (e.g., Luck & Vogel, 1997 ; Oberauer & Lin, 2017 ; van den Berg et al, 2012 ; Zhang & Luck, 2008 ), the three-parameter mixture model of Bays et al ( 2009 ) has been most commonly applied to template-guided visual search (Dube & Al-Aidroos, 2019 ; Hollingworth & Hwang, 2013 ; Huynh Cong & Kerzel, 2020 ; Kerzel, 2019 ; Kerzel & Witzel, 2019 ; Rajsic et al, 2017 ; Rajsic & Woodman, 2019 ). In this model, three distributions contribute to the likelihood of a given response.…”
Section: Wm Resources and Visual Searchmentioning
confidence: 99%